EFEK PENAMBAHAN ESTRAK DAUN PEPAYA TERHADAP PERTUMBUHAN IKAN GURAMI (Osphronemus goramy) - Zulkhasyni, Zulkhasyni; Djatmiko, Djatmiko; Dani, Ramat; Pardiansyah, Dedi; Yulfiperius, Yulfiperius (University of Prof. Dr. Hazairin, SH, 2023)
This research aims to determine the effect of giving papaya leaf extract on the growth of gourami fish (Osphronemus goramy). This research was carried out in May - June 2021 in Bengkulu City for 60 days. The test fish used were gourami fish measuring 6-8 cm. The method used was a Completely Randomized Design (CRD) with 4 treatments, namely P1: Without papaya leaf extract (control), P2: Dose of papaya leaf extract (10%), P3: Dose of papaya leaf extract (20%), P4: Dose of extract papaya leaves (30%). Each treatment was repeated six times. The research data was analyzed using analysis of variance then continued with further tests for BNT 5% and 1%. The research results of adding papaya leaf extract to the growth of gourami fish for 60 days had a very significant effect on the parameters of absolute weight, absolute length, feed conversion and feed efficiency and had no effect on the survival of the gourami fish. The best treatment for the growth of gourami fish is an additional dose of 20% - 30% papaya leaf extract.